CONSERVATISM IN ACCOUNTING: FINANCIAL DISTRESS, TAX AND LITIGATION RISK - Andres P Sitepu; Tommy Munaf; Hasnarika Hasnarika; Raja Yulianita Sarazwati; Putri Dwi Novrina; Jumadil Saputra (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
In the application of accounting conservatism plays an important role in assessing the earnings quality of a financial report. If financial statements are made using conservative principles, they tend to reflect the company's financial condition which is not true. The concept of conservatism is often used by companies that trade their shares openly. For example, a company listed on the Indonesia Stock Exchange is a forum for companies or issuers to trade their company shares. With the aim of obtaining additional capital needed by the company in carrying out its operational activities. This study consists of three independent variables Financial Ditress (X1), Litigation Risk (X2) and Tax (X3). And the dependent variable is accounting conservatism. The object of research is a company listed on the Indonesia Stock Exchange from 2018 to 2020. The data used in this study amounted to 135 data. The data analysis technique uses the Eview10 application by using regression model analysis, classical assumption testing and hypothesis testing